A Higher Frequency of CD4+CXCR5+ T Follicular Helper Cells in Adult Patients with Minimal Change Disease. (27th August 2014) - Zhang, Nan; Zhao, Pingwei; Shrestha, Amrita; Zhang, Li; Qu, Zhihui; Liu, Mingyuan; Zhang, Songling; Jiang, Yanfang
Abstract : Background . T follicular helper (TFH) cells are involved in the humoral immune responses. This study is aimed at examining the frequencies of different subsets of CD4 + CXCR5 + TFH cells in adult patients with minimal change disease (MCD). Methods . A total of 27 patients and 14 healthy controls (HC) were characterized for the levels of sera cytokines, inducible T-cell costimulator (ICOS), and programmed death 1 (PD-1) of positive TFH cells by flow cytometry. The level of sera IL-21 was examined; 24 h urinary protein and eGFR were calculated. The potential correlation between the frequency of different subsets of TFH cells and the values of clinical measures in MCD patients were analyzed. Results . The frequency of circulating CD4 + CXCR5 +, CD4 + CXCR5 + ICOS +, and CD4 + CXCR5 + PD-1 + TFH cells and the levels of sera IL-17A, IFN- γ, IL-2, IL-10, IL-4, and IL-21 were significantly higher in MCD patients (P < 0.05 ) than that in the HC group. Furthermore, the percentages of circulating CD4 + CXCR5 + TFH cells were negatively correlated with the values of eGFR (r = - 0.4849, P < 0.05 ) and the percentages of CD4 + CXCR5 + PD-1 + TFH cells were correlated positively with the levels of serum IL-21 (r = 0.6137, P < 0.05 ) and 24 h urinary protein (r = 0.1410, P < 0.05 ) in those patients. Also, the percentages of CD4 + CXCR5 + ICOS + TFH cells were correlated positively with the levels of serum IL-21 (r = 0.6201, P < 0.05 ) and 24 h urinary protein (r = 0.7519, P < 0.05 ). Following standard therapies, the percentages of circulating CD4 + CXCR5 +, CD4 + CXCR5 + PD-1 +, and CD4 + CXCR5 + ICOS + TFH cells and the levels of serum IL-21 were significantly reduced, but the levels of serum IL-4 and IL-10 were increased (P < 0.05 ). Conclusions . A higher frequency of CD4 + CXCR5 + TFH cells that existed in adult patients with MCD could be new target for intervention of MCD.